2008
DOI: 10.1073/pnas.0710799105
|View full text |Cite
|
Sign up to set email alerts
|

Rational chemical design of the carbohydrate in a glycoconjugate vaccine enhances IgM-to-IgG switching

Abstract: Many pathogens are sheltered from host immunity by surface polysaccharides that would be ideal as vaccines except that they are too similar to host antigens to be immunogenic. The production of functional IgG is a desirable response to vaccines; because IgG is the only isotype that crosses the placenta, it is of particular importance in maternal vaccines against neonatal disease due to group B Streptococcus (GBS). Clinical studies found a substantially lower proportion of IgG-relative to IgM-among antibodies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 48 publications
1
36
1
Order By: Relevance
“…1D). These data suggest that there are intra-and interspecies variations in the immunogenic properties exerted by the sialic acid moiety (49)(50)(51).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…1D). These data suggest that there are intra-and interspecies variations in the immunogenic properties exerted by the sialic acid moiety (49)(50)(51).…”
Section: Resultsmentioning
confidence: 88%
“…Some bacterial CPS motifs, including sialic acid, are very similar to molecules expressed by human cells or tissues, which could result in immune evasion through molecular mimicry (69). Therefore, chemical alteration of sialic acid of N. meningitidis type B CPS by de-N-acetylation or deletion of this sugar in GBS type V CPS improved the immunogenicity of these two CPSs (50,70). However, the consequences of capsular sialic acid manipulation on the capacity of CPS to acti-…”
Section: Discussionmentioning
confidence: 99%
“…3A). (40,41). SBA assays were performed with pooled sera collected 2 wk after the second and the third immunization against the same strain used for MenX PS production, and indicated that antibodies induced by immunization with the MenX-CRM 197 conjugates were functional (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages can efficiently internalize latex beads to form nascent phagosomes displaying all their properties, such as maturation protein markers like LAMP1 (12,23). To obtain CPSlinked latex beads, we adapted a technique commonly used to conjugate a protein carrier to CPS (21), replacing the protein by a latex bead with amine groups at its surface, which covalently link purified CPS. We obtained an artificial particle about the size of a bacterium, which allowed us to discriminate biological effects on phagocytes directly related with CPS without interference from other virulence factors.…”
Section: Discussionmentioning
confidence: 99%